(untitled) (Scientia Agropecuaria, 2021)
The oil of debittered and dehulled grains from two Andean lupins (Lupinus mutabilis) from Peru, Andenes and Común, was extracted by expeller press. The extraction yield and the proximal composition of both varieties were assessed. The oil and the cake, as well as the defatted flour from the variety with the highest extraction yield, were characterised for physico-chemical properties, total polyphenol content and antioxidant capacity. The oil shelf-life at 25 °C was extrapolated by Rancimat test. Andenes presented an oil yield of 22.1% (vs. 18.4% of Común), CIELAB colour coordinates of L* = 36.5, a* = 2.2, b* = 20, refractive index and density at 25 ºC of 1.469 and 0.903 g/mL, acid number of 3.2 mg KOH/g, free fatty acids content of 1.6%, peroxide number of 2.7 meqO2/kg, p-anisidine number of 1.3, unsaponificable content of 58%, total antioxidant capacity 21.4 µmol TE/g and total polyphenol content of 7.0 mg AGE/100 g. The predominant fatty acid, tocopherol and phytosterol in the oil were oleic acid (56.2%), γ-tocopherol (555 mg/kg) and β-sitosterol (41900 mg/100 g), respectively. The oil shelf-life at 25 ºC was 2.7 years. The Lupinus mutabilis oil extracted by expeller presented an acceptable quality with a lower environmental negative impact than the oils obtained by solvent extraction.